Detection of blood vessels under the skin by using a thermal camera operating within (Negative mode) and processing the resulting thermal image using the Python programming language (Damascus University Journal for the basic sciences, 2025)
This research focused on detecting blood vessels under the skin with the aim of showing them in people who suffer from some diseases such as obesity, newborns and many other medical conditions, by relying on the thermal differences between the blood vein in which blood flows and the tissue that surrounds it. For this purpose, I used a thermal camera that works in negative mode and captures long-wave infrared rays and focuses them on the matrix sensor, which in turn converts the thermal rays into an electronic signal and displays it on the computer connected to the thermal camera within a computerprogram dedicated to the camera. The resulting image is marred by noise resulting from the surrounding environment and many factors. The other is why the image was subjected to processing to increase the contrast in the image by writing software code in the programming language (Python) so that the blood vessels become distinct from the surrounding tissues.This research was applied to the forearms of a group of people. Five cases were selected, including five people. The distribution of local temperatures on the forearms was recorded. It was experimentally found that the temperature of the forearm was on average (31.98℃) and the range of tissue temperature ranged within the range (24.3-32.0) ℃, The temperature range of blood veins ranges within the range (30.6-34.5) ℃.
Keywords: Blood vessels under the skin; Thermal differences; Thermal camera; Negative mode; thermal objective; Software code